The Current State of Built Heritage in Karachi: The Case of Empress Market - Soomro, Tania Ali; Shah, Ayesha Agha; Pasha, Yasira Naeem (Journal of Art, Architecture and Built Environment, 2020)
Modern Karachi has a fragmented and multifaceted social formation, while its historic core presents a diverse range of historical attributes of its built heritage. The increasing urban population of Karachi contributes heavily to its degradation including the degradation of its historical attributes. There is no effective heritage legislation and there are conflicts between what people do and what the government institutions do. Consequently, there is chaos and deterioration in the inner city. The city has been developing rapidly and the government has proposed many projects for the revival of the historic core of the city. However, most of them have not been successful. The objective of this research is to examine the situation in which heritage buildings face a serious threat. The current research focused on one such project, that is, the Empress Market ̶ the restoration and redevelopment of its historic precinct. It adopted physical observations, archival analysis, and site surveys along with photographic documentation and interviews of the local shop dwellers (especially to focus on the historical evolution of the building) as research techniques. The findings showed that the state of deprivation of the historic core of Karachi is the reflection of a collective devastation of the precinct in terms of social and historic values, which is further supported by the non-prevailing heritage legislative system. The research also investigates the present condition of the Empress Market in connection with its glorious past and urban decay befallen to it over time due to vandalism and the numerous restoration plans proposed for it over the years. The study can be beneficial to comprehend the ground realities concerning the survival of heritage properties within the cumulative urbanization process. The results can be used also to propose the rejuvenation of the lost splendor of the historic urban core of Karachi as a prototype for parallel development schemes.